Prevalence and Risk Factors of Occupational Contact Dermatitis in Healthcare Workers - Enggalhardjo, Muljani; Setiawan, Alan Dwi; Christianto, Putra Niko Laksamana Oceano (Fakultas Kedokteran Universitas Pelita Harapan, 2024)
Background: Occupational contact dermatitis (OCD) is prevalent among healthcare workers, especially during the COVID-19 pandemic. Symptoms include dryness, itchiness, and redness, with hands being the most affected. Risk factors include frequent hand washing, increased glove use, allergies, and lack of health and safety training. This review emphasizes the need for targeted prevention strategies and awareness programs.Methods: We conducted a systematic review using PubMed, focusing on studies involving healthcare workers and OCD. Keywords included